Peran Kepala Sekolah sebagai Penggerak Manajemen BK: Menguatkan Layanan Konseling di Era Kurikulum Merdeka - M. Fazli; Yarmis Syukur; Neviyarni N (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Guidance and counseling (BK) services play a crucial role in supporting students' academic, emotional, social, and career development. In the era of the Independent Curriculum, with its emphasis on individual potential development and learning flexibility, the need for effective BK services is becoming increasingly crucial. This study aims to analyze the role of the Principal (KS) as a driving force and manager in optimizing BK management in schools. The method used is a literature study by examining various empirical studies and theories on BK management, school leadership, and the implementation of the Independent Curriculum. The results of the study indicate that KS has a strategic role in: (1) providing structural support facilities/infrastructure and policies; (2) encouraging collaboration between BK teachers, homeroom teachers, and subject teachers; (3) conducting supervision and monitoring; (4) ensuring the integration of BK services into the school education system. However, many cases show that BK management is not optimal due to a lack of commitment, resources, or understanding of the BK function. Therefore, the role of the KS as a driving force is crucial to the success of counseling services in the era of the Independent Curriculum. Recommendations are given for strengthening commitment, training, and a structured BK management system.